Effect of butyrate on NO secretion from hypoxic human umbilical vein endothelial cells and its underlying mechanism - YANG Chengzhong; YANG Chengzhong; YANG Chengzhong; FENG Lan; FENG Lan; FENG Lan; CHEN Dewei; CHEN Dewei (Di-san junyi daxue xuebao, 2020)
Objective To investigate the molecular mechanism of hypoxia-decreased NO secretion in vascular endothelial cells, and to explore the intervention role of butyrate (Bur) in the process. Methods Human umbilical vein endothelial cells (HUVECs) were divided into normoxia group (21% O2), hypoxia group (1% O2), hypoxia plus solvent control group, hypoxia plus Bur group (4 mmol/L Bur), hypoxia plus control siRNA group, and hypoxia plus HDAC3 siRNA group. The NO content in the supernatant was tested by NO Assay Kit. The mRNA expression of endothelial nitric oxide synthetase (eNOS) was detected by RT-PCR, and its protein level and that of histone deacetylase 3 (HDAC3) were measured by Western blotting. The interaction of HDAC3 to eNOS was analyzed by co-immunoprecipitation. Results Compared with the normoxia group, hypoxia for 6 h resulted in significant decrease in the NO level in the supernatant (P < 0.05), and reduced eNOS protein level though no change in its mRNA level. In the hypoxic HUVECs, HDAC3 protein level did not changed when compared with the normoxia group. Co-immunoprecipitation analysis showed that hypoxia induced the interaction of HDAC3 with eNOS, and suppressed the acetylation of eNOS protein. The level of eNOS protein was obviously increased in the hypoxia plus HDAC3 siRNA group than the hypoxia plus control siRNA group. Compared with the hypoxia plus solvent control group, the level of NO secretion and eNOS protein were increased significantly in hypoxia plus Bur group (both P < 0.05), but the interaction between the HDAC3 and eNOS was decreased and acetylation of eNOS protein was increased. Conclusion Hypoxia induces HDAC3-eNOS binding and inhibits acetylation of eNOS protein, which might be due to its destruction in eNOS stability and suppression in NO secretion. While, Bur treatment can reverse above process in vascular endothelial cells.